One-stop computerized virtual planning system for the surgical management of posterior wall acetabular fractures - Jianan Chen; Yifan Zheng; Zhixun Fang; Wei Zhou; Dan Xu; Guodong Wang; Xianhua Cai; Ximing Liu (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Posterior wall acetabular fractures remain one of the most difficult fracture injuries to treat. Accurate assessment of fracture characteristics and appropriate preoperative surgical strategies are essential for excellent reduction. This paper evaluates the feasibility and effectiveness of a one-stop computerized virtual planning system for the surgical management of posterior wall acetabular fractures. Methods 52 cases of posterior wall acetabular fractures treated surgically were selected in our department between January 2015 and December 2020 for retrospective analysis. 52 cases were classified into group A (25 patients) and group B (27 patients) according to whether computerized virtual planning procedures were performed preoperatively. In group A, virtual surgical simulation was conducted using a one-stop computerized planning system preoperatively. In group B, traditional surgery was employed. Reduction quality, surgical time, blood loss, hip function, complications, and instrumentation time were compared between the two groups. Results The actual surgery for all patients in group A was essentially the same as the virtual surgery before the operation. Compared to group B, patients in group A had markedly shorter surgical time (−43 min), shorter instrumentation time (−20 min), and less intraoperative blood loss (−130 ml). However, no significant statistical difference was observed in reduction quality and hip function. The complication rate was slightly lower in group A (4/25) than in group B (7/27), without a significant difference. Conclusion The one-stop computerized virtual planning system is a highly effective, user-friendly and educational tool for allowing the cost-efficient surgical simulation of posterior wall acetabular fractures and providing a more individualized therapeutic schedule. The one-stop computerized planning system is feasible to treat posterior wall acetabular fractures, which is an effective method than the conventional treatment of posterior wall acetabular fractures. Trial registration: retrospective registration.